Nanoparticles in Targeted Drug Delivery System - Vaidehi Acharya; Hemadri Sharma (Asian Journal of Pharmaceutical Research and Development, 2026)
Nanotechnology has emerged as a transformative approach in modern pharmaceutical sciences, particularly in improving drug delivery system[1,3]. Nanoparticles, due to their unique physicochemical properties, enable targeted delivery of therapeutic agents to specific sites within the body. This thesis explores the principles, types, mechanisms, advantages, limitations, and applications of nanoparticles in targeted drug delivery. Special emphasis is placed on their role in enhancing bioavailability, reducing toxicity, and improving therapeutic efficacy [7,16]. The study also highlights recent advancements and future perspectives in nanomedicine.